Optimal Stabilization Policies for Deterministic and Stochastic Linear Systems: Comments - Chang, S. S. L.; Stekler, H. O. (Review of Economic Studies, 1976)
S. S. L. Chang, H. O. Stekler; Optimal Stabilization Policies for Deterministic and Stochastic Linear Systems: Comments, The Review of Economic Studies, Volume